Galileo on Theology's Status as a Science. (Heythrop Journal, 2022)
The article explores the Galilean corpus on theology's status as a science relating to inferences by Alfredo Damanti. Topics discussed are inferiority of theology to natural philosophy and mathematics, superiority of theology due to nobility of its subject matter which are salvation, ordering of things to heaven and earth and grace, polysemy of Scriptural language, distinction of faith and morals from nature, and Catholic theology's determine of the true sense of Scriptural passages.